TRADISI SONGKABALA PERSPEKTIF HUKUM ISLAM - Zulfajrin Nur; Abdul Halim Talli; Ibnu Izzah (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam)
Abstract The core of the problem discussed is about the Songkabala Tradition from the Perspective of Islamic Law (Case Study in the Batulabbu Community, Bantaeng Regency. The type of research used in this research is qualitative. The sources of this research are community leaders, traditional leaders, religious leaders and several related institutions. Songkabala which is understood by the Batulabbu community is prayer, barazanji and shalawat. The goal is to ask Allah SWT for protection from reinforcements and dangers. Songkabala in Batulabbu community there are two, namely songkabala 10 muharram and songkabala Dangerous appalili, for the implementation of 10 muharram it is carried out in the mosque and for danger appalili carried out at the house of the residents who carry it out. In the implementation also has its own differences. Songkabala is still maintained by the Batulabbu community and has a great influence in the village. The view of Islamic law in terms of songabala processions such as praying for protection and safety for songkabala is not contradictory because this is intended for Allah SWT. The view of Islam in terms of public relations to the songkabala tradition here, Islam does not prohibit, on the contrary, it is to strengthen ties of friendship. The view of Islamic law in terms of food and ingredients, Islam does not recommend preparing certain foods and ingredients. Islam only recommends praying, except making food only to be eaten together after the prayer is permissible. Keywords: Tradition, Songkabala, Islamic Law Perspectiv